Desenvolvimento de uma bancada didática para ensaios de névoa salina - MESCOUTO, Cláudio Fernando da Costa (2023)
Resistance is a natural process that can result in damage and fluctuating costs for the industry. The different types of resistance include uniform bands, plate, alveolar, punctiform, intergranular and filiform. To control the corrosive process, cyclic resistance tests, such as the salt spray (fog) accelerated corrosion chamber, are performed to simulate natural resistance in the laboratory. These tests provide important information about the mechanism of the corrosive process and help identify the most suitable metallic material and coating for each corrosive environment. Furthermore, prevention and control of resistance can generate savings, both direct and indirect. This paper discusses the importance of cyclic resistance tests in simulating natural resistance in the laboratory and how these tests work to prevent and control resistance.